Tectonic Stresses and Injection-Induced Fault Slip Assessment - Yaghoubi, Ali (University of Waterloo, 2022)
Understanding the Earth's stress state at depth is fundamental to a wide variety of subsurface projects, ranging from seismology projects to studies on underground energy storage or extraction. The primary objectives of this dissertation are first to constrain the state of stress by combining drilling-induced wellbore failures and earthquake focal mechanisms, and second to use a probabilistic approach for stresses, pore pressures and rock properties to assess injection-induced fault slip in unconventional and geothermal resources. Knowledge of the state of stress in an area helps us understand the seismic hazard and crustal-scale seismicity pattern issues (>10 km); the energy development (3-6 km) issues from hydrocarbon to geothermal resources; the reservoir scale issues (0.1-1 km) of induced seismicity arising from energy extraction; and borehole scale engineering issues (up to 100 m) related to casing shear and borehole stability. As part of this dissertation, I measure the orientation and constrain the magnitude of present-day stresses in the Dezful Embayment within Iran’s Zagros Fold and Thrust Belt (ZFTB), Alberta's Fox Creek area, the Montney Formation in Alberta and British Columbia, and Alberta's Grande Prairie area. The ZFTB in southwest Iran is one of the world's most seismically active areas. The Dezful Embayment (DE) within the ZFTB is also one of the richest hydrocarbon regions in the world, hosting many onshore hydrocarbon fields. Western Canada is also home to some of the largest oil and gas reserves in the world, including unconventional resources such as the Montney and Duvernay Formations. The injection-induced earthquakes in western Canada have some of the largest magnitudes reported worldwide, such as those near Fort St. John in British Columbia and Fox Creek in Alberta. Considering the economic importance of the region and the seismic activity in these areas, it is important that we gain a better understanding of the state of stress in ZFTB and Western Canada. It is noteworthy that tectonic stresses have not been studied on such a large scale in these regions. To understand the state of stress in each region, two datasets were used. The first included petrophysical data from drilled wells, and the second contained natural and injection-induced earthquake focal mechanisms. Formal stress inversion analysis of the tectonic earthquake focal mechanisms in ZFTB demonstrates that there is currently a compressional stress state in the basement below the sediments. The seismologically determined SHmax direction is NE-SW, nearly perpendicular to the strike of most faults in the region. However, borehole geomechanics analysis in the ZFTB region using rock strength and drilling evidence leads to the counterintuitive result that the shallow state of stress is a normal/strike-slip regime. Based on Coulomb faulting theory, these results indicate that a reverse fault regime with a maximum horizontal principal direction of SW-NE is unfavorable for slip along the N-S strike-slip basement Kazerun Fault System. In Alberta and British Columbia, a similar approach but using injection-induced earthquakes indicates that strike-slip faulting with NE-SW SHmax directions dominates the region. It has been observed that relative stress magnitudes are primarily related to pore pressure variation in Alberta and British Columbia. In the compartmentalized Montney Formation of western Alberta and northeastern British Columbia, these characteristics are evident. Stress measurements will always contain some level of uncertainty due to either inadequate data or inherent uncertainties. These uncertainties impact any project in which the stress plays a central role at different scales. Therefore, probabilistic methods are necessary to quantify the impact of these uncertainties on each project. The uncertainty invariably associated with the state of stress measurements affects the analysis of subsurface events such as seismicity induced by hydraulic fracture (HF) stimulation. HF for energy extraction from underground conventional, unconventional, and geothermal resources is typically accompanied by anthropogenic seismicity. Increasing pore pressure by injecting fluid into naturally fractured media leads to slip/shearing of faults and fractures, resulting in detectable earthquakes. The magnitude and rate of such human-made earthquakes are directly related to stress orientations and magnitudes. This uncertainty in the stress state, plus a variety of uncontrollable subsurface parameters including the original pore pressure, size, and density of pre-existing faults/fractures, fault/fracture orientation, and frictional strength make up the most important factors affecting the probabilistic assessment of fault/fracture slip. In HF treatments, accounting for parametric uncertainty by using appropriate statistical probability distributions leads to better decision-making/risk management for user-controlled parameters such as injection pressure. Historically quiet areas in Alberta and eastern British Columbia have experienced noticeably higher seismicity rates over the last decade. Shale gas and shale oil production from the unconventional plays in the Western Canada Sedimentary Basin has grown with the use of multi-stage HF (Hydraulic Fracture stimulation) technology. Supported by high oil prices and new HF technology availability, development started in 2005 and accelerated significantly in 2011; accordingly, the seismicity rate has increased. The anthropogenic seismicity for this area includes some of the largest MW values reported globally, including events near Fort St. John of MW 4.6 on August 17, 2015, and MW 4.2 on November 30, 2018. Most of these occur during HF treatments and are spatially and temporally restricted to the region around the wells at a scale of 1-2 km, rather than being regional at a scale of more than two kilometers. As part of this dissertation, the probability assessment of fault/fracture slip due to fluid injection has been used and implemented in three different case studies. These include Alberta’s Fox Creek area, the Montney Formation of western Alberta and northeastern British Columbia, and Alberta’s Grande Prairie area. In each case study, geomechanics parameters are expressed as probability distributions using different datasets from borehole petrophysical data to injection-induced focal mechanisms. Monte Carlo simulations are applied to assess the potential slip tendency of local faults. The cumulative distribution function of critical pore pressure to cause slip on each known fault is developed by using analyses of the Mohr-Coulomb shear parameters and local tectonic stress state. Injection-induced seismicity in the region is a formation-related phenomenon governed by the in-situ formation conditions and pre-existing fault patterns. A map is developed that can be used to predict which area of the Montney Formation is at greater risk of earthquakes caused by fracking. Probabilistic maps of fault stability can provide a basis for future fluid injection projects, such as wastewater disposal, hydraulic fracture stimulation, CO2 storage, and geothermal energy extraction.